PERKAWINAN BEDA AGAMA DALAM PERSPEKTIF HADIS AHKAM - Muhammad Farid (Al-Bayyinah, 2017)
Abstract Ideal marriage in Islam cover both physical and psyche aspects. Specially in psyche spectrum, the same in a belief is a main stream. Islam always warns to the all Muslims not to marry a follower of the different religion. Cause if it does the for bidden, the next: main target of marriage, namely life in loving and happy each other, it wont be fulfilled except one the converts. If it converts to Islam, it may be not a problem, but if one of them out of Islam, it is a really case. So syariat Islam warns to marry with the one of the similarity life ideologi, and it will be explain in the next item.Kata Kunci: Perkawinan, beda agama, hadis ahkam, konversi dan ijtihad ulama